ROA, ROE, CAR, and EPS on The Stock Price of PT Bank Mandiri (Persero) Tbk with GARCH (1,1) - Nova Elindasari (Indonesian Financial Review, 2021)
This study aims to analyze the effect of  ROA, ROE,  CAR, and EPS on the stock prices at PT. Bank Mandiri (Persero) Tbk in 2010-2019. Technical analysis uses simple linear regression analysis and GARCH (1,1), hypothesis testing using the t-test parsial regression coefficient testing coefficient with a level of significance of 5% (0.05). In addition, These data is non parametric because it has multicollinearity and autocorrelation. These results indicate that only show the results of GARCH (1,1) that ROA and EPS has significant effect on stock return PT Bank Mandiri Tbk.